TINJAUAN SYARIAH TERHADAP TRANSAKSI MUAMALAT ASURANSI KESEHATAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) (IAIN Tulungagung, 2016)
Insurance business can be distinguished on some reviews. It includes generalinsurances, life insurances and reinsurances (on the basis of its function).Based on its basic policy, it includes term life insurances, whole life insurances,two beneficial insurances, insurances of investment unit (unit linked). Basedon its belongings, it includes national private-owned insurances, state-ownedinsurances, foreign corporations-owned insurances, and multiplicity-ownedinsurances. Based on the nature of its implementation, it includes voluntaryand compulsory insurances. Based on the business support activities, it includesinsurance brokers, reinsurance brokers, insurance loss assessor, consultingactuary, and insurance agents. Mean while, mechanisms of Takaful (shari’ainsurances) include underwriting, insurance policies, premiums, managementof premiums, claims and insurance coverage. The main obstacles to developshari’a insurance are lack of socialization, limitation of human resources ofTakaful’s expert; lack of Muslim support, weakness of government support.Keywords: Insurance, Shari’a, BPJS.IAIN Tulungagung, Jl. Mayor Sujadi Timur No. 46Email:budikolistiawan@gmail.com